A Review of the Use of Investigative Projects in Statistics and Data Science Courses - Allison Davidson (Journal of Statistics and Data Science Education, 2024)
AbstractAn investigative project can engage the learner in all aspects of a statistical investigation, including developing a question or issue of interest, gathering needed information, exploring the data, and communicating the results. This article summarizes the available literature regarding the implementation of investigative projects, including the potential benefits of projects, how projects have been used in a variety of settings, advice for those looking to implement projects, and future research avenues.